Les effets physiologiques de l’amour : une critique de l’épistémologie d’Empédocle dans le Phèdre, 251a-252b - Emma Ponce (Études Platoniciennes)
Abstract: The aim of this article is to elucidate an allusion to the epistemology of Empedocles in the passage from the central myth of the Phaedrus in which Plato describes the physiological symptoms experienced by the lover when he sees his beloved and the wings of his soul begin to grow (251a-252b). The method used to do this is to distinguish the different levels of meaning superimposed in the Platonic text. First of all, the physiological clues in the passage allow a medical reading of the growth of the wings, which reveals a reference to the Empedoclean theory that the unification of sensations can lead to a knowledge that goes beyond sensible experience. The discovery of this reference sheds light on the metaphor of the growth of the wings of the soul: it refers to the Platonic process of dialectical synthesis, which elevates from the sensible to the intelligible, and provides a correction of Empedocles' theory. Finally, the concrete experience of love, which is the apparent object of the passage, reveals that Plato took up the Empedoclean theme of love in order to subordinate unity to the Good, against Empedocles, and thus to found the method of unification.